Pengaruh Pengelolaan Dana Desa Dalam Meningkatkan Pembangunan Desa Popalo Kecamatan Anggrek Kabupaten Gorontalo Utara - Wandri Pakaya; Muhammad Amir Arham; Roy Hasiru; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The research employed a quantitative approach with a descriptive research method where the data were obtained by distributing questionnaires to the Popalo village community, including the Popalo village government. In the meantime, the population of this research was the entire Heads of Household, totaling 347 people, including the village government registered in Popalo Village, Anggrek Subdistrict, Gorontalo Utara Regency. Meanwhile, the research samples were 30 respondents or 30 Heads of Household. At the same time, the data analysis technique used was the product-moment correlation statistical formula. The findings depicted that the village fund positively and significantly affected the development of Popalo Village, Anggrek Subdistrict, Gorontalo Utara Regency. This finding signified that the good implementation of village fund by the government could improve the development of Popalo Village, Anggrek Subdistrict, Gorontalo Utara Regency.